It is currently 13 Dec 2017, 18:44

# Decision(s) Day!:

CHAT Rooms | Ross R1 | Kellogg R1 | Darden R1 | Tepper R1

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# If k#0 and k - (3 -2k^2)/k = x/k, then x =

Author Message
TAGS:

### Hide Tags

Math Expert
Joined: 02 Sep 2009
Posts: 42583

Kudos [?]: 135550 [0], given: 12697

If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink]

### Show Tags

24 Feb 2014, 22:50
Expert's post
9
This post was
BOOKMARKED
00:00

Difficulty:

35% (medium)

Question Stats:

57% (00:51) correct 43% (00:58) wrong based on 763 sessions

### HideShow timer Statistics

The Official Guide For GMAT® Quantitative Review, 2ND Edition

If $$k\neq{0}$$ and $$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$, then x =

(A) -3 - k^2
(B) k^2 -3
(C) 3k^2 - 3
(D) k - 3 - 2k^2
(E) k - 3 + 2k^2

Problem Solving
Question: 111
Category: Algebra Second-degree equations
Page: 76
Difficulty: 500

GMAT Club is introducing a new project: The Official Guide For GMAT® Quantitative Review, 2ND Edition - Quantitative Questions Project

Each week we'll be posting several questions from The Official Guide For GMAT® Quantitative Review, 2ND Edition and then after couple of days we'll provide Official Answer (OA) to them along with a slution.

We'll be glad if you participate in development of this project:
2. Please vote for the best solutions by pressing Kudos button;
3. Please vote for the questions themselves by pressing Kudos button;
4. Please share your views on difficulty level of the questions, so that we have most precise evaluation.

Thank you!
[Reveal] Spoiler: OA

_________________

Kudos [?]: 135550 [0], given: 12697

Math Expert
Joined: 02 Sep 2009
Posts: 42583

Kudos [?]: 135550 [0], given: 12697

Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink]

### Show Tags

24 Feb 2014, 22:50
Expert's post
3
This post was
BOOKMARKED
SOLUTION

If $$k\neq{0}$$ and $$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$, then x =

(A) -3 - k^2
(B) k^2 -3
(C) 3k^2 - 3
(D) k - 3 - 2k^2
(E) k - 3 + 2k^2

$$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$;

Multiply by k: $$k^2 - (3 -2k^2) = x$$;

$$x=3k^2-3$$.

_________________

Kudos [?]: 135550 [0], given: 12697

Manager
Status: GMATting
Joined: 21 Mar 2011
Posts: 108

Kudos [?]: 108 [1], given: 104

Concentration: Strategy, Technology
GMAT 1: 590 Q45 V27
Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink]

### Show Tags

25 Feb 2014, 22:26
1
KUDOS
k - \frac{3 -2k^2}{k} = \frac{x}{k};
After simplifying and canceling k in the denominator, we get: k^2 - 3 + 2k^2 = x;
3k^2 - 3 = x;

Ans is (C).

Kudos [?]: 108 [1], given: 104

Senior Manager
Joined: 20 Dec 2013
Posts: 267

Kudos [?]: 111 [2], given: 29

Location: India
Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink]

### Show Tags

26 Feb 2014, 01:10
2
KUDOS
Option C.
k-(3-2k^2)/k=x/k
Multiply both sides by k
k^2-3+2k^2=x
3k^2-3=x

Kudos [?]: 111 [2], given: 29

SVP
Status: The Best Or Nothing
Joined: 27 Dec 2012
Posts: 1849

Kudos [?]: 2788 [0], given: 193

Location: India
Concentration: General Management, Technology
WE: Information Technology (Computer Software)
Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink]

### Show Tags

08 Jul 2014, 21:17
Bunuel wrote:
SOLUTION

If $$k\neq{0}$$ and $$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$, then x =

(A) -3 - k^2
(B) k^2 -3
(C) 3k^2 - 3
(D) k - 3 - 2k^2
(E) k - 3 + 2k^2

$$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$;

Multiply by k: $$k^2 - (3 -2k^2) = x$$;

$$x=3k^2-3$$.

I just added a step after the highlighted one to remove -ve sign . Rest all did same

$$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$;

$$k + \frac{2k^2 - 3}{k} = \frac{x}{k}$$
_________________

Kindly press "+1 Kudos" to appreciate

Kudos [?]: 2788 [0], given: 193

Veritas Prep GMAT Instructor
Joined: 16 Oct 2010
Posts: 7792

Kudos [?]: 18119 [0], given: 236

Location: Pune, India
Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink]

### Show Tags

08 Jul 2014, 22:55
Bunuel wrote:
The Official Guide For GMAT® Quantitative Review, 2ND Edition

If $$k\neq{0}$$ and $$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$, then x =

(A) -3 - k^2
(B) k^2 -3
(C) 3k^2 - 3
(D) k - 3 - 2k^2
(E) k - 3 + 2k^2

You can also put in k = 1 in $$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$ to get x = 0.
When you put k = 1 in options, only (C) and (E) give x = 0.

Now put k = -1 in $$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$ to get x = 0.
When you put k = -1 in options, only (C) gives x = 0
_________________

Karishma
Veritas Prep | GMAT Instructor
My Blog

Get started with Veritas Prep GMAT On Demand for $199 Veritas Prep Reviews Kudos [?]: 18119 [0], given: 236 Current Student Joined: 14 Oct 2013 Posts: 47 Kudos [?]: 8 [0], given: 120 Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink] ### Show Tags 10 Mar 2015, 19:07 Why do we automatically assume there are parentheses around (3-2k^2)? I didn't assume that so then I didn't distribute the negative on the outside which of course then gave me answer A. Kudos [?]: 8 [0], given: 120 Math Expert Joined: 02 Aug 2009 Posts: 5347 Kudos [?]: 6119 [1], given: 121 Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink] ### Show Tags 10 Mar 2015, 19:28 1 This post received KUDOS Expert's post soniasawhney wrote: Why do we automatically assume there are parentheses around (3-2k^2)? I didn't assume that so then I didn't distribute the negative on the outside which of course then gave me answer A. hi soniasawhney.. it does not require any parenthesis as any sign in front of a fraction modifies the entire fraction irrespective of the term.. just an example.. let the fraction be - $$\frac{7-9}{2}$$.. two ways to do it .. first change signs first and then find answer... $$\frac{-7+9}{2}$$=$$\frac{2}{2}$$=1... second simplify and then change the signs... - $$\frac{7-9}{2}$$=- $$\frac{-2}{2}$$=-(-1)=1.. so both ways answer is same, which means parentheses is not required and a sign in front of a fraction automatically means that the entire fraction is inside bracket.... _________________ Absolute modulus :http://gmatclub.com/forum/absolute-modulus-a-better-understanding-210849.html#p1622372 Combination of similar and dissimilar things : http://gmatclub.com/forum/topic215915.html Kudos [?]: 6119 [1], given: 121 Veritas Prep GMAT Instructor Joined: 16 Oct 2010 Posts: 7792 Kudos [?]: 18119 [2], given: 236 Location: Pune, India Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink] ### Show Tags 10 Mar 2015, 20:24 2 This post received KUDOS Expert's post soniasawhney wrote: Why do we automatically assume there are parentheses around (3-2k^2)? I didn't assume that so then I didn't distribute the negative on the outside which of course then gave me answer A. To clarify further: There are 3 ways in which you can make a fraction negative $$\frac{-3}{5}$$ $$-\frac{3}{5}$$ Take this to mean $$\frac{-3}{5}$$ and $$\frac{3}{-5}$$ Each one of these fractions is the same as $$\frac{-3}{5}$$ Now what happens in case you have multiple terms in numerator: $$\frac{-x + 2}{4}$$ The negative is only in front of x. $$-\frac{x+2}{4}$$ The negative is in effect, in front of the entire numerator. So this is the same as $$\frac{-(x+2)}{4}$$ _________________ Karishma Veritas Prep | GMAT Instructor My Blog Get started with Veritas Prep GMAT On Demand for$199

Veritas Prep Reviews

Kudos [?]: 18119 [2], given: 236

SVP
Joined: 06 Nov 2014
Posts: 1903

Kudos [?]: 550 [0], given: 23

Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink]

### Show Tags

12 Mar 2015, 22:12
Bunuel wrote:
The Official Guide For GMAT® Quantitative Review, 2ND Edition

If $$k\neq{0}$$ and $$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$, then x =

(A) -3 - k^2
(B) k^2 -3
(C) 3k^2 - 3
(D) k - 3 - 2k^2
(E) k - 3 + 2k^2

Problem Solving
Question: 111
Category: Algebra Second-degree equations
Page: 76
Difficulty: 500

GMAT Club is introducing a new project: The Official Guide For GMAT® Quantitative Review, 2ND Edition - Quantitative Questions Project

Each week we'll be posting several questions from The Official Guide For GMAT® Quantitative Review, 2ND Edition and then after couple of days we'll provide Official Answer (OA) to them along with a slution.

We'll be glad if you participate in development of this project:
2. Please vote for the best solutions by pressing Kudos button;
3. Please vote for the questions themselves by pressing Kudos button;
4. Please share your views on difficulty level of the questions, so that we have most precise evaluation.

Thank you!

Given that,
k - (3 - 2k^2)/k = x/k
Take LCM of denominators,
So, [k^2 - (3 - 2k^2)]/k = x/k
So, [k^2 - 3 + 2k^2]/k = x/k
Canceling out k from the denominators of both sides,
So, [k^2 - 3 + 2k^2] = x
So, 3k^2 - 3 = x
Hence option C.

--
Optimus Prep's GMAT On Demand course for only $299 covers all verbal and quant. concepts in detail. Visit the following link to get your 7 days free trial account: http://www.optimus-prep.com/gmat-on-demand-course Kudos [?]: 550 [0], given: 23 Intern Joined: 31 Oct 2013 Posts: 3 Kudos [?]: [0], given: 2 Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink] ### Show Tags 07 Apr 2016, 15:29 I'm not sure whats wrong here: 1. k - [3-2k^2][/k] = [x][/k] 2. k - 3 + 2k^2 = x I am assuming I can't move the denominator to the right side because of the first term (k), just not sure why. Kudos [?]: [0], given: 2 SVP Joined: 06 Nov 2014 Posts: 1903 Kudos [?]: 550 [2], given: 23 Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink] ### Show Tags 10 Apr 2016, 19:06 2 This post received KUDOS Apollon wrote: I'm not sure whats wrong here: 1. k - [3-2k^2][/k] = [x][/k] 2. k - 3 + 2k^2 = x I am assuming I can't move the denominator to the right side because of the first term (k), just not sure why. 1. k - [3-2k^2][/k] = [x][/k] 2. k - 3 + 2k^2 = x Hi Apollon, If you see, only two of the three terms have the denominator k. In order to cancel out the denominator from all the terms, you need to have the same denominator in each term. In the given case, 1. k - (3-2k^2)/ k = x / k We need to make sure that the denominator of the first term is also the same. Hence k^2/k - (3-2k^2)/ k = x / k From here on, we can cancel the terms. k^2 - 3 + 2k^2 = x Or x = 3k^2 - 3 Option C Does this help? Kudos [?]: 550 [2], given: 23 Veritas Prep GMAT Instructor Joined: 16 Oct 2010 Posts: 7792 Kudos [?]: 18119 [1], given: 236 Location: Pune, India Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink] ### Show Tags 10 Apr 2016, 22:10 1 This post received KUDOS Expert's post Apollon wrote: I'm not sure whats wrong here: 1. k - [3-2k^2][/k] = [x][/k] 2. k - 3 + 2k^2 = x I am assuming I can't move the denominator to the right side because of the first term (k), just not sure why. Yes, you re right. To move the denominator to the other side, it must be the denominator of the entire expression. Look at it from a very basic viewpoint: 1/2 = x 1 = 2x Since x is 1/2, twice of x will be 1. 1 + 1/2 = x 1 + 1 = 2x ???? x is actually 3/2 or (1.5). If you double it, will you get 2? No. On the other hand, (1 + 3+ 5)/2 = x Then (1 + 3 + 5) = 2x is correct. _________________ Karishma Veritas Prep | GMAT Instructor My Blog Get started with Veritas Prep GMAT On Demand for$199

Veritas Prep Reviews

Kudos [?]: 18119 [1], given: 236

Manager
Status: On a 600-long battle
Joined: 21 Apr 2016
Posts: 138

Kudos [?]: 25 [0], given: 392

Location: Hungary
Schools: Erasmus '20
GMAT 1: 410 Q18 V27
GMAT 2: 490 Q35 V23
Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink]

### Show Tags

30 Apr 2017, 00:33
VeritasPrepKarishma wrote:
soniasawhney wrote:
Why do we automatically assume there are parentheses around (3-2k^2)? I didn't assume that so then I didn't distribute the negative on the outside which of course then gave me answer A.

To clarify further:
There are 3 ways in which you can make a fraction negative
$$\frac{-3}{5}$$

$$-\frac{3}{5}$$ Take this to mean $$\frac{-3}{5}$$

and $$\frac{3}{-5}$$

Each one of these fractions is the same as $$\frac{-3}{5}$$

Now what happens in case you have multiple terms in numerator:

$$\frac{-x + 2}{4}$$ The negative is only in front of x.

$$-\frac{x+2}{4}$$ The negative is in effect, in front of the entire numerator. So this is the same as $$\frac{-(x+2)}{4}$$

Thank you, VeritasPrepKarishma

I too fell for this rule.

So basically in this exercise.

$$-\cfrac { 3-2{ k }^{ 2 } }{ k } \neq \cfrac { -3-2{ k }^{ 2 } }{ k } \\ \\ -\cfrac { 3-2{ k }^{ 2 } }{ k } \rightarrow \cfrac { -\left( 3-2{ k }^{ 2 } \right) }{ k }$$
_________________

"When the going gets tough, the tough gets going!"

|Welcoming tips/suggestions/advices (you name it) to help me achieve a 600|

Kudos [?]: 25 [0], given: 392

Re: If k#0 and k - (3 -2k^2)/k = x/k, then x =   [#permalink] 30 Apr 2017, 00:33
Display posts from previous: Sort by